Concept of Scarcity in Conventional Economics; A Critical Analysis With Islamic Economic Perspective-Konsep Scarcity Dalam Ekonomi Konvensional; Sebuah Analisis Kritis Dengan Perspektif Ekonomi Islam - Lahuri, Setiawan Bin; Dwi Rahayu, Hesti Maharani (Jurnal Ilmiah Ekonomi Islam, 2024)
This scarcity issue is still a hot topic every year. In conventional economics, scarcity is defined as a lack of natural resources that can be used and utilized by a society, which ultimately leads to a riot and insatisfaction with the needs of a society. Deficiency is seen as a problem that has yet to be solved in its economic activities. They divide the type of deficiency into two types: absolute deficiency and relative deficiency. While Islamic economics does not recognize the type of deficiency that is absolute. In Islam, the absolute is the abundance of resources, but what is to be limited is the human desire. Islam only knows the relative deficiency caused by the desires of humans that exceed the use of the existing resources. In this study, the author will criticize the concept of scarcity in conventional economics using critical analysis from the perspective of Islamic economics. This research uses the method of library research, which collects data from quoting and analyzes it against various pieces of literature that have relevance to the issues discussed, then reviews and concludes. The results of this study show a very fundamental difference between the concept of scarcity in conventional economics and the Islamic concept. The Islamic economy does not recognize the kind of deficiency that is absolute in nature. In Islam, the absolute is the abundance of resources, but what is to be limited is the human desire. Islam only knows the relative deficiency caused by the desires of humans that exceed the use of the existing resources. In the Islamic perspective, the human condition should not be lack or poverty, but well-being and abundance. Being abundant means that the real condition is sufficient to satisfy all the needs of man; this is the natural condition of the world and not something to be anticipated or expected.